Histone Demethylase JMJD3 Mediated Doxorubicin-Induced Cardiomyopathy by Suppressing SESN2 Expression - Wang, Panxia; Lan, Rui; Guo, Zhen; Cai, Sidong; Wang, Junjian; Wang, Quan; Li, Zeyu; Li, Zhenzhen; Wang, Qianqian; Li, Jingyan; Wu, Zhongkai; Lu, Jing; et al. (Frontiers in Cell and Developmental Biology, 2020)
Jumonji domain-containing 3 (JMJD3) protein, a histone demethylase protein, specifically catalyzes the demethylation of H3K27 (H3K27me3) and regulates gene expression. Sestrin2 (SESN2), a stress-inducible protein, protected against doxorubicin (DOX)-induced cardiomyopathy by regulating mitophagy and mitochondrial function. Here, the expression of JMJD3 was increased and that of SESN2 was decreased in both the heart samples from patients with dilated cardiomyopathy and chronic DOX-stimulation induced cardiomyopathy. Inhibition or knockdown of JMJD3 attenuated DOX-induced cardiomyocytes apoptosis, mitochondrial injury and cardiac dysfunction. However, JMJD3 overexpression aggravated DOX-induced cardiomyopathy, which were relieved by SESN2 overexpression. JMJD3 inhibited the transcription of SESN2 by reducing tri-methylation of H3K27 in the promoter region of SESN2. In conclusion, JMJD3 negatively regulated SESN2 via decreasing H3K27me3 enrichment in the promoter region of SESN2, subsequently inducing mitochondrial dysfunction and cardiomyocytes apoptosis. Targeting the JMJD3-SESN2 signaling axis may be a potential therapeutic strategy to protect against DOX-mediated cardiomyopathy.